Provable Data Recoverability and Hide-Able Access Pattern Based ORAM - Hongwei Li; Feiyue Ye; Dan Chen (Dianxin kexue)
With the development and application of cloud computing, more and more customers choose cloud storage as the storage medium, therefore, data integrity and privacy become a major problem that the customers concern. A new structure based on oblivious RAM model was proposed. The customer file was composed by data blocks of equal-sized, and each data block had two backups in the cloud storage, and they were randomly stored in different cloud files in order to ensure data integrity. Oblivious RAM allowed a client to hide its data access patterns from an untrusted server. The data possession was verified to utilize homomorphic hash algorithm. The adversary can not obtain useful information from the client access data pattern, and the data privacy is guaranteed.